Pendanaan Kampanye di Pemilu Serentak 2019 di Indonesia: Penguatan Demokrasi Patronase? - Sukmajati, Mada; Disyacitta, Fikri (Integritas : Jurnal Antikorupsi, 2019)
This paper examines the patterns of campaign funding in the Indonesian 2019 Concurrent Election by focusing on the dimensions of revenue and expenditure both in the presidential and legislative elections. This article also discusses the nature of the political regime as a consequence of the patterns. In doing so, the analysis is based on campaign finance theory supported by the concept of clientelism and programmatic politics. By relying on secondary data, this paper argues that the way the candidates manage their campaign funding shows the strengthening of political clientelism on one side and the waning of programmatic politics on the others side. Consequently, patronage democracy will also strengthen in Indonesia after the 2019 Election. Keywords: Campaign Funding, Presidential Election, Legislative Election, Clientelism, Patronage